Ways to improve the reliability of the nodes of the rolling mill (Modern Problems of Metallurgy, 2020)
The performance of the crimping mill is determined by the speed of the pressure device. The main purpose of the pressure device is to regulate the relative position of the rolls, which is necessary to ensure the rolling of the profile of a given size and predetermined reductions, and in reversing mills, the distance between the rolls changes almost after each pass.An industrial survey of crimping rolling mills has shown that their reliability and durability significantly depend on the working capacity of the friction units, one of which is a screw pair of a pressure device. At this time, there is no information in the literature on the patterns of wear intensity of turns of screw pairs of rolling mills.Basically, increasing the resistance of nuts is done by balancing the load on the threads by changing the shape of the body of the nut. All these structural improvements of the nuts of the screw pair of the pressing mechanisms should be taken into account at the stage of designing the rolling stand, since changing the external shape of the nut can cause inevitable downtime of the production line associated with the coordination of seats in the bed of the rolling mill, which are unacceptable in the conditions of continuous production.In order to increase the working capacity of the screw pair of the pressing mechanism of the crimping mill, the task was set to analytically study the influence of the design of the threaded connection of the screw pair of the pressing mechanism on its efficiency.For crimping mills, in contrast to rolling a strip or sheet, more important is the speed of the pressure mechanism. An increase in the thread pitch leads to an increase in the efficiency of the helical gear, but the use of a thread with a large pitch has limitations associated with the displacement of the average diameter to the projections of the thread, reducing its reliability and the accuracy of the gap between the rolling rolls. Screw thread - single thrust resistant. If you thread according to current standards, only the friction angle in the thread remains - a factor that can be varied with an increase in the efficiency of the screw pair.The decrease in the angle of friction in the thread, with its proportional dependence on the coefficient of friction-slip, causes a significant increase in the efficiency of the screw pair. Reducing the coefficient of friction-slip is possible by the correct selection of rubbing pairs and the timely supply of lubricant to the friction zone. Since in the process of rolling technological operations, moments may occur when the lubricant is not supplied to the friction zone, one of the ways to increase the efficiency of the threaded joint should be the option of the correct selection of friction pairs that are less affected by the lack of lubricant supply to the friction zone.
Keywords: crimping machine, pressure mechanism, screw steam, thread, coefficient of friction